1996
DOI: 10.1161/01.cir.93.7.1411
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Pathophysiology of Carotid Sinus Syndrome

Abstract: This study strongly suggests that the neuromuscular structures surrounding the carotid mechanoreceptors are involved in the carotid sinus syndrome; however, the exact mechanism remains speculative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Debate has often centered on whether the peripheral receptor is indeed "hypersensitive" or whether the fault lies centrally in the manner in which the afferent signals are processed [19]. The latter argument has been supported by the findings of Tea et al [23]. These investigators have suggested that the electromyographic analysis of the sternocleidomastoid (SCM) muscle differed significantly between the groups.…”
Section: Relationships Between Hbes and Syncopal Reactionsmentioning
confidence: 99%
“…Debate has often centered on whether the peripheral receptor is indeed "hypersensitive" or whether the fault lies centrally in the manner in which the afferent signals are processed [19]. The latter argument has been supported by the findings of Tea et al [23]. These investigators have suggested that the electromyographic analysis of the sternocleidomastoid (SCM) muscle differed significantly between the groups.…”
Section: Relationships Between Hbes and Syncopal Reactionsmentioning
confidence: 99%
“…We do not believe this invalidates our findings for two reasons: firstly, we did not provide an afferent stimulus to any other muscle groups during our CSM protocol so they presumably did not ameliorate the impact of our intervention; secondly, prior research has shown that only reductions in EMG of the sternocleidomastoid muscles, and not other neck muscles (such as styloglossus and upper trapezius) were associated with CSH (Tea et al 1996). …”
Section: Limitationsmentioning
confidence: 77%
“…One leading idea postulates that, in healthy individuals, stimulation of the sternocleidomastoid muscles near the carotid baroreceptors (during neck turning or carotid sinus massage), as well as the carotid baroreceptors themselves, leads to central integration of the two signals as “external” stretching of the sinus, and thus does not elicit a baroreflex response (Tea et al. 1996). Loss of this central integration due to sternocleidomastoid denervation might lead to hypersensitive responses during daily activities, such as neck turning, as well as during CSM (Blanc et al.…”
Section: Introductionmentioning
confidence: 99%
“…Performance of advanced tests is appropriate in patients when no specific syncope etiology could be revealed by patient history, physical examination and ECG. Recent studies have reported that a detailed history taking and meticulous physical examination may be sufficient for determining a specific syncope etiology in 49-85 % of patients 17 . Sheldon et al reported that 86 % of cases could not be diagnosed 14 .…”
Section: Discussionmentioning
confidence: 99%